Attitudes of editors of core clinical journals about whether systematic reviews are original research: a mixed-methods study - Krnić Martinić, Marina; Herrle, Florian (BMJ open, 2019)
Objectives  In 2009, not all journal editors considered systematic reviews (SRs) to be original research studies, and not all PubMed Core Clinical Journals published SRs. The aim of this study was to conduct a new analysis about editors’ opinion regarding SRs as original research. Design  We conducted a survey and qualitative interview study of journal editors. Participants  All editors listed as editor-in chief of 118 PubMed Core Clinical Journals. - Methods  We contacted editors via email and asked them whether they considered SRs original research, whether they published SRs in the journal and, if yes, in which section. We searched PubMed for any SRs (or metaanalyses) published in the included journals in 2017; if we did not find any, we hand-searched these journals. Editors were invited to participate in a follow-up qualitative interview study. - Results  We received responses from 73 editors representing 72 (62%) journals. Fifty-two (80%) editors considered SRs original research, either for any type of SR (65%) or only for SRs with a meta-analysis (15%) and almost all (91%) of editors published SRs. Compared with the results of the 2009 study of Core Clinical Journals, a similar proportion of editors considered SRs to be original studies (71%), accepted SRs as original on certain condition such as presence of meta-analysis (14%) or published SRs (94%). Interviews with editors showed that they used various criteria to decide whether a SR is original research, including methodology, reproducibility, originality of idea and level of novelty. - Conclusion  The majority of editors of core clinical journals consider that SRs are original research. Among editors, there was no uniform approach to defining what makes a SR, or any study, original. This indicates that the concepts of originality of SRs and research are evolving and that this would be a relevant topic for further discussion.
Gesehen am 14.04.2020